Manajemen Pengembangan Objek Wisata Pantai Bonebula di Desa Towale Kecamatan Banawa Tengah Kabupaten Donggala - Janna, Nadyatul; Nuraisyah; Royfandi, Moh. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
ABSTRACT The purpose of this research is to examine the management in the development of Bonebula Beach Tourism Object in Towale Village, Banawa Tengah District, Donggala Regency. The basis of this research is descriptive qualitative, the number of informants is 7 people. Data collection techniques are observation, interviews, and documentation. The results of the study indicate that the planning aspect (Planning) in the planning aspect of the local government through the Tourism Office has scheduled superior programs in the development of tourism objects in the Donggala Regency environment including in Towale Village, but this has not been able to be implemented optimally due to budget constraints. The organizational aspect (Organizing) of Bonebula Beach tourism can be said to have run well. Management is carried out jointly between the village government, the community through the Tourism Awareness Group (POKDARWIS), and supported by the Tourism Office. The actuating aspect of Bonebula Beach tourism has gone through the planning and organizing stages. However, activities such as direction, guidance, and communication to human resources are still not optimal and need to be improved, including attention to tourism facilities. Supervision (Controlling) Supervision at the Bonebula Beach Tourist Attraction has been running well and the Tourism Office routinely conducts evaluations and mentoring every weekend or holiday. In addition, tourism managers are also actively guarding the area, both day and night, especially during activities such as camping. Development management has been running quite well due to the reality on the ground regarding the seriousness of the local government, especially the Donggala Regency Tourism Office, in carrying out management functions that are carried out in a structured manner. However, in implementing tourism development there are still several factors that become obstacles due to budget limitations and the still lack of involvement of human resources in terms of developing and maintaining Bonebula Beach tourism.